EVALUATION OF THE USE OF KWARA STATE PUBLIC LIBRARY BY SECONDARY SCHOOL STUDENTS IN ILORIN METROPOLIS - Laaro, Dolapo Medinat; Oyedokun, Tunde Toyese; Ambali, Olanihun Zainab (Edulib, 2019)
The study investigated the relevance of public library to the peculiar needs of secondary school students in Ilorin Metropolis. A descriptive research design was adopted for the study and 300 students participated in the survey. The instruments for data collection include structure questionnaire, interview as well as personal observation. Each instrument complements one another and the data gathered were analyzed through the calculation of frequencies and percentages. Reports of findings has it that Kwara State Library Board stand a good chance to adequately cater for the diverse educational and other related information needs of secondary school students in Ilorin Metropolis, but yet such expectation have not been met to a large extent. The state library has not leave up to its responsibility of providing services that support school curriculum and education. It is on this basis that recommendation was made that appropriate ministry responsible for funding of public library should wake up to reality of what is expected of a modern public library.